Human Genomic Safe Harbors and the Suicide Gene-Based Safeguard System for iPSC-Based Cell Therapy. (19th March 2019) - Kimura, Yasuyoshi; Shofuda, Tomoko; Higuchi, Yuichiro; Nagamori, Ippei; Oda, Masaaki; Nakamori, Masayuki; Onodera, Masafumi; Kanematsu, Daisuke; Yamamoto, Atsuyo; Katsuma, Asako; Suemizu, Hiroshi; Nakano, Toru; et al.
Abstract : The use of human induced pluripotent stem cells (hiPSCs) and recent advances in cell engineering have opened new prospects for cell-based therapy. However, there are concerns that must be addressed prior to their broad clinical applications and a major concern is tumorigenicity. Suicide gene approaches could eliminate wayward tumor-initiating cells even after cell transplantation, but their efficacy remains controversial. Another concern is the safety of genome editing. Our knowledge of human genomic safe harbors (GSHs) is still insufficient, making it difficult to predict the influence of gene integration on nearby genes. Here, we showed the topological architecture of human GSH candidates, AAVS1, CCR5, human ROSA26, and an extragenic GSH locus on chromosome 1 (Chr1-eGSH). Chr1-eGSH permitted robust transgene expression, but a 2 Mb-distant gene within the same topologically associated domain showed aberrant expression. Although knockin iPSCs carrying the suicide gene, herpes simplex virus thymidine kinase ( HSV-TK ), were sufficiently sensitive to ganciclovir in vitro, the resulting teratomas showed varying degrees of resistance to the drug in vivo. Our findings suggest that the Chr1-eGSH is not suitable for therapeutic gene integration and highlight that topological analysis could facilitate exploration of human GSHs for regenerative medicine applications. Our data indicate that the HSV-TK/ganciclovir suicide gene approach alone may be not an adequate safeguard against the risk of teratoma, and suggest that the combination of several distinct approaches could reduce the risks associated with cell therapy. Stem Cells Translational Medicine 2019;8:627&638 : Abstract : Tumorigenesis and the risks associated with genome editing are major concerns of human induced pluripotent stem cells-based therapies. In this report, we list the features of human genome safe harbor candidates and demonstrate that topological analysis facilitates prediction of the influence of genome editing. We also suggest that the herpes simplex virus thymidine kinase suicide gene system alone would not be an adequate safeguard.